State-level factors in Metropolitan Climate Activism - Carl M. Hand; Dana Williams (Journal of Public and Professional Sociology)
As nation states equivocate over meaningful climate change agreements, hundreds of cities worldwide and in the US have joined to promote climate change policies and actions. Many US cities have taken a leadership role in promoting ameliorative public policy and best practices, overcoming significant disincentives for doing so, particularly low levels of public salience and unreliable federal support and resources. Several of these evolving networks are now in existence, including the United States Conference of Mayors Climate Protection Agreement. The US Conference of Mayors plays a significant role in facilitating best practices as well as recognizing cities on the vanguard of climate leadership. Research to date has examined the factors explaining metropolitan climate activism, including potential climate risk, the influence of carbon intensive industries at the local level, and the role of community environmental capital. Less understood is the role that state-level energy policy and socio-political factors play influencing metropolitan climate activism. This research underscores the significance of political partisanship, both in terms of state environmental politics and statewide Democratic voting record, for understanding metropolitan climate activism.